STRATEGI PERSONAL BRANDING DALAM PEMENANGAN PEMILU LEGISLATIF (STUDI KASUS IR. RIDWAN BAE DI SULAWESI TENGGARA) - Sumaryono Sumaryono; Niken Febrina Ernungtyas; Guntur Freddy Prisanto (Universitas Tidar, 2021)
Personal branding studies have become popular in the last decade, but have been practically used for a long time. Personal branding is widely implemented in celebrities, social media and including politics. In the political context, personal branding is one of the strategies for winning elections. Especially in Indonesia it happened because of the change from representative democracy to direct democracy. This has resulted in every Indonesian citizen being able to directly elect candidates for political leadership at both national and local levels. This study aims to describe the personal branding strategy of legislative candidates in the election. Personal branding in the legislature has not appeared much in academic discourse compared to personal branding of the president or regional head. The research used a qualitative approach with a case study of Ir. Ridwan Bae is a politician from the Golkar Party in the Southeast Sulawesi constituency. Three informants were interviewed in a structured and in-depth manner. The results of the interviews were analyzed by thematic analysis using three stages of qualitative coding. Based on the results of the analysis, there are three personal branding strategies, namely image, rational attribution and emotional attribution. In forming this image, there are three important things to pay attention to, namely the general description of the persona, uniqueness and authenticity. Rational attributes used in personal branding strategies are leadership, ability, credibility and consistency. Finally, there are three elements of emotional attributes, namely being role models, party attributions and values.